ChemInform Abstract: Photocatalytic Synthesis of Glycosyl Bromides. Issue 29 (22nd July 2014) - Yuan, Xiaolong; Cheng, Sen; Shi, Yanbin; Xue, Weihua
Abstract A simple protocol for the conversion of sugar hemiacetals into the corresponding glycosyl bromides under mild reaction conditions is developed.